2019
DOI: 10.1055/a-0893-5838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subcutaneous Tissue on Changes in Thigh Circumference Following Anterior Cruciate Ligament Reconstruction

Abstract: Circumference measurements have been used to estimate muscle cross-sectional area (CSA) in clinical settings. Measurements of thigh circumference are affected by muscle and subcutaneous fat (SF). In fact, SF could increase over a short period. Therefore, clarifying the relationship between thigh circumference and muscle and SF following ACL reconstruction is important. This study’s primary purpose was to examine pre- and post-operative changes in thigh circumference, thigh muscles and SF CSAs in both legs. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a study by Otzel et al [ 32 ], 24 ACLR participants were recruited from a university campus, and no significant difference was found in thigh circumference between legs; however, strength deficits were found in the ACLR limb compared to the uninvolved leg. A previous study reported that the thigh circumference of the ACLR limb underestimated thigh atrophy and quadricep weakness persistence, averaging 48 months post-surgery [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Otzel et al [ 32 ], 24 ACLR participants were recruited from a university campus, and no significant difference was found in thigh circumference between legs; however, strength deficits were found in the ACLR limb compared to the uninvolved leg. A previous study reported that the thigh circumference of the ACLR limb underestimated thigh atrophy and quadricep weakness persistence, averaging 48 months post-surgery [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sequelae of graft failure, especially OA, are still clinically challenging problems [ 3 , 23 , 24 , 25 , 26 ]. However, the cause of OA is multifactorial and long-term outcomes after ACL injury and post-ACLR are influenced by many associated factors, such as the status of the articular cartilage, meniscus, BMI, state of the quadriceps muscles, and knee joint laxity [ 5 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research by Wade et al and Housh et al reported a strong correlation between thigh circumference and thigh muscle CSA at the mid-thigh [5,6]. On the other hand, Yoshii et al showed a significant correlation between thigh circumference and quadriceps CSA (r=0.73) at the 5 cm level, which was not significant at the 5 and 15 cm level (r=0.31, and 0.42, respectively) [7], indicating the importance of the measurement level in predicting the muscle volume. In this study, the CSAs of the vastus medialis, vastus lateral & vastus intermedius, and all muscles revealed a strong correlation with thigh circumference at 10 cm above the patella (r>0.68), supporting the clinical routine performed at hospitals.…”
Section: Discussionmentioning
confidence: 86%